2019
DOI: 10.1055/s-0039-3400204
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Residual Syntax Score after Percutaneous Coronary Intervention in Multivessel Coronary Artery Disease

Abstract: Background Residual SYNTAX (Synergy between Percutaneous Coronary Intervention with Taxus and Cardiac Surgery) Score (RSS) is an objective measure for the assessment of degree and complexity of residual stenosis after the percutaneous coronary intervention (PCI). Aim The study aimed at evaluating the role of angiographic complete (CR) and incomplete (ICR) revascularization on clinical outcomes in patients undergoing PCI for multivessel coronary artery disease (MVCAD). The study sought to investigate the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Several studies have reported adverse short and long-term outcomes associated with incomplete revascularization. 15,16 The evidence from a meta-analysis conducted in this aspect has shown that the risk of adverse outcomes can be reduced by achieving complete revascularization in STEMI patientsparticularly in those with MVD. 17 In our study, patients had a mean age of 50.10±10.74 years with a mean age of 49.56±10.24 years in cases and 50.64±11.25 years in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported adverse short and long-term outcomes associated with incomplete revascularization. 15,16 The evidence from a meta-analysis conducted in this aspect has shown that the risk of adverse outcomes can be reduced by achieving complete revascularization in STEMI patientsparticularly in those with MVD. 17 In our study, patients had a mean age of 50.10±10.74 years with a mean age of 49.56±10.24 years in cases and 50.64±11.25 years in controls.…”
Section: Discussionmentioning
confidence: 99%